Effect of Contingency Leadership, Competence, and Personality Traits on the Productivity of Permanent Lecturers of Private Universities Mediated by Compensation - Thasimmim , Said Nuwrun; Johannes , Johannes; Yacob , Syahmardi; Junaidi , Junaidi (Insight: the psychological dimensions of society, 2025)
Purpose. The low productivity of permanent lecturers in Private Higher Education Institutions (PHEI) in the Riau Islands Province is a critical issue requiring immediate scholarly attention. This situation poses significant challenges in competing with foreign labor in the region, highlighting the urgent need to enhance human resources through targeted educational strategies. The study aims to systematically investigate the multifaceted factors contributing to this phenomenon, focusing on the influences of contingency leadership, professional competence, and personality traits of lecturers. Additionally, the research explores the role of compensation as a mediating variable that potentially impacts lecturer productivity. Methods. Employing an explanatory quantitative approach, the research involved a sample of 260 permanent lecturers selected from a total population of 935, utilizing Hair’s formula for sampling adequacy. A descriptive analysis was conducted to elucidate respondents’ perceptions, while the five-box method was employed for comprehensive response evaluation. Subsequently, Structural Equation Modeling (SEM) was used to yield in-depth insights into the interrelationships among the examined variables. Results. The findings reveal that contingency leadership, professional competence, and personality traits of lecturers exert a positive influence on productivity levels. However, a low understanding of functional positions among lecturers emerges as a significant impediment. Furthermore, compensation was identified as having a substantial effect on productivity; nonetheless, the overall productivity of lecturers remains categorized as low. Discussion and Conclusions. The implications of this research underscore the paramount importance of implementing contingency leadership within higher education management frameworks and recognizing the significance of personality traits in human resource strategies. A thorough evaluation of compensation systems and the adjustment of management policies are crucial for enhancing lecturer productivity. These findings provide a foundational basis for developing effective strategies aimed at improving lecturer productivity in private universities, particularly in the Riau Islands Province. This research uniquely contributes to the field of human resource management in higher education by offering practical insights that can be integrated into university policies concerning leadership, resource competence, and lecturer compensation.